2007
DOI: 10.1681/asn.2006080863
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Clearance of Protein-Bound Solutes by Addition of a Sorbent to the Dialysate

Abstract: The capacity of sorbent systems to increase solute clearances above the levels that are provided by hemodialysis has not been well defined. This study assessed the extent to which solute clearances can be increased by addition of a sorbent to the dialysate. Attention was focused on the clearance of protein-bound solutes, which are cleared poorly by conventional hemodialysis. A reservoir that contained test solutes and artificial plasma was dialyzed first with the plasma flow set at 46 ؎ 3 ml/min and the dialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
101
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 25 publications
3
101
0
Order By: Relevance
“…Alternative treatment regimens were shown to increase clearances, but their impact on circulating levels, overall, was limited if not negligible. Adsorptive techniques, though promising from an efficacy point of view, are limited by high costs and/or non-selective adsorption causing inferring a high risk of thrombotic complications [94,95].…”
Section: Increasing the Removal Of Colon-derived Toxinsmentioning
confidence: 99%
“…Alternative treatment regimens were shown to increase clearances, but their impact on circulating levels, overall, was limited if not negligible. Adsorptive techniques, though promising from an efficacy point of view, are limited by high costs and/or non-selective adsorption causing inferring a high risk of thrombotic complications [94,95].…”
Section: Increasing the Removal Of Colon-derived Toxinsmentioning
confidence: 99%
“…Efforts are mounting to reduce serum concentrations, either by reducing intestinal uptake (4) or by improving blood clearances (5,6).…”
mentioning
confidence: 99%
“…Indoxyl sulfate and p-cresyl sulfate are perhaps the most widely used marker molecules to study the behavior of the protein-bound uremic retention solutes during hemodialysis, hemodiafiltration, peritoneal dialysis, and experimental adsorption-based blood purification devices (5)(6)(7)(8)(9)(10). In addition, both indoxyl sulfate and p-cresyl sulfate are thought to contribute directly to uremic syndrome (1).…”
mentioning
confidence: 99%
“…Another method that may enhance the ef iciency of removal of proteinbound uremic retention solutes, such as IS and PCS, is addition of a sorbent to the dialysate, which may achieve increases in clearance of more than two-fold 54 . Furthermore, a pilot study using two dialyzers in series showed an enhanced clearance of IS and PCS (by 57% and 66%, respectively) by increasing the dialyzer mass transfer area coef icient and dialysate low compared to conventional practice 55 .…”
Section: Dialysismentioning
confidence: 99%